Relationship between density and recoverability in social networks - Gallego, Tulio Andrés Clavijo; Castillo, Verenice Sánchez (AWARI, 2023)
The paper explores elements of the existing literature to investigate the complex relationship between the density of social networks and their resilience to shocks. Density and recoverability are key concepts in understanding the strength of social networks. It discusses how a dense social network can facilitate communication recovery by providing multiple pathways for reorganization and mutual support among users. However, it can also lead to rigidity and vulnerability to targeted attacks or systematic failures. The importance of an optimal balance between the density of a network and the diversity of its connections to maximize its recoverability is explored, along with the role of digital technology and social networking platforms in changing these dynamics. The article concludes with recommendations for future research and other considerations for designing and managing resilient social networks, focusing on the need for a better understanding of the interplay between network structures, social dynamics, and the external factors that influence them.